TO STUDY GLOMERULAR FILTRATION RATE IN ESSENTIAL HYPERTENSION. - MANISH R; MEERA K S (International Journal of Pharma and Bio Sciences, 2014)
Hypertension is one of the major causes of morbidity and mortality in human population. High blood pressure is a well established threat factor for cardiovascular disease partly because it is proatherogenic and also it facilitates injury to the vascular endothelium via increased stress caused by the flowing of blood. The objective of the study was to determine GFR in prehypertensives and essential hypertensives. Serum creatinine was estimated in autoanalyser by alkaline picrate method and eGFR was calculated using MDRD equation. There is significant decrease in S. creatinine level and increase in eGFR value in prehypertensives as compared to controls. But there is a significant decrease in eGFR value in hypertensives as compared to controls and prehypertensives. The study indicates measuring glomerular filtration rate is a better indicator of ongoing pathophysiological mechanisms and progression of the disease above the measurement of arterial pressure and serum creatinine level in both prehypertensives and hypertensives.